Non-small cell lung cancer recurrence following surgery and perioperative chemotherapy: Comparison of two chemotherapy regimens (IFCT-0702: A randomized phase 3 final results study). Issue 2 (August 2015) - Moro-Sibilot, Denis; Audigier-Valette, Clarisse; Merle, Patrick; Quoix, Elisabeth; Souquet, Pierre-Jean; Barlesi, Fabrice; Chouaid, Christos; Molinier, Olivier; Bennouna, Jaafar; Lavolé, Armelle; Mazières, Julien; Toffart, Anne-Claire; et al.
Highlights: Doublet or monotherapy for patients pretreated with chemotherapy and surgery? We compared docetaxel with platinum docetaxel in relapsed patients after surgery. Survival characteristics were in the range of chemotherapy-naïve Stage IV. Improved response rate, with the doublet but no significant effect on PFS nor OS. This subset of patients should be treated like chemonaive patients. Abstract: Introduction: This study compared the efficacy of docetaxel alone vs. docetaxel plus cisplatin/carboplatin in resected NSCLC patients relapsing after preoperative, adjuvant, or perioperative platinum-based chemotherapy. Materials and methods: Patients were randomly assigned to receive docetaxel plus cisplatin/carboplatin (Arm A) or docetaxel alone (Arm B). Primary endpoint was progression-free survival (PFS). Secondary endpoints were response rate at 6 weeks, toxicity, quality of life, and overall survival (OS). Results: From November 2007 to August 2012, 88 patients were enrolled. Due to an unexpectedly slow accrual, the trial was prematurely stopped. Adding platinum to docetaxel caused a non-significant increase in PFS. Median PFS was 8.0 months (95% CI: 5.3–10.4) for Arm A vs. 5.6 months (95% CI: 4.0–7.3) for Arm B (HR: 0.71, 95% CI: 0.45–1.1, p = 0.15). Median OS was 16.0 months (95% CI: 10.1–23.9) for Arm A vs. 12.4 months (95% CI: 8.2–19.6) for Arm B. In pre-planned subgroup analyses, a time to recurrence ≥12 months and non-squamous histology favorably influenced OS (HR: 0.51, 95% CI: 0.29–0.91, p = 0.02 and HR: 0.54, 95% CI: 0.33–0.91, p = 0.02, respectively). There were no unexpected adverse events, and Grade 3–4 toxicity was comparable in both groups. Conclusions: Our study failed to demonstrate significant PFS improvement with the docetaxel-platinum doublet compared to single-agent docetaxel. The 3.6-month improvement in OS with the cisplatin-based doublet proves, however, appealing and merits further investigation.